2015
DOI: 10.1185/03007995.2015.1011780
|View full text |Cite
|
Sign up to set email alerts
|

Does a cardiovascular event change adherence to statin treatment in patients with type 2 diabetes? A matched cohort design

Abstract: The occurrence of a drug-treated cardiovascular event appeared to avert the declining statin adherence rate observed in diabetes patients without such an event. On the other hand, one in five patients became less adherent after the event, indicating that there are still important benefits to achieve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
2
11
2
Order By: Relevance
“…They also found that patients with a greater baseline comorbidity burden were less likely to change from nonadherent to adherent and were more likely to change from adherent to nonadherent after an AMI. Another study with 855 patients with type 2 diabetes mellitus found that 26% of patients became more adherent and 20% of patients became less adherent after incident cardiovascular events . However, we found strong relationships with adherence change after AMI associated with race/ethnicity and CABG during hospitalization that were not found in these earlier studies.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…They also found that patients with a greater baseline comorbidity burden were less likely to change from nonadherent to adherent and were more likely to change from adherent to nonadherent after an AMI. Another study with 855 patients with type 2 diabetes mellitus found that 26% of patients became more adherent and 20% of patients became less adherent after incident cardiovascular events . However, we found strong relationships with adherence change after AMI associated with race/ethnicity and CABG during hospitalization that were not found in these earlier studies.…”
Section: Discussioncontrasting
confidence: 92%
“…Change in adherence to statins after an AMI has been reported in a few prior studies . In a study that used a 5% random sample of Medicare patients, Kronish et al found that 33% of patients with pre‐AMI PDC ≥80% became nonadherent after an AMI, while 38% of patients with PDC <80% became adherent after AMI.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…While several studies have shown that health events, such as cancer diagnosis, pregnancy, or AMI, can increase smoking cessation,(2,33) there are few data showing that health events can positively influence medication adherence. (19) Several small studies show that clinicians can enhance the effect of the teachable moment by drawing clear connections between the health event and preventive health behaviors when counseling patients. (34,35) Thus, our study implies that clinicians can promote statin adherence after AMI by explicitly linking the prevention of recurrent cardiac events to medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…(1215) Previous studies have documented substantial nonadherence to statins after hospitalization for AMI,(1618) but few data have been published on changes in adherence to statins from before to after an AMI hospitalization. (19) Determining the impact of an AMI hospitalization on adherence to statins after discharge can guide clinical expectations of statin adherence and can inform the design of interventions to improve adherence.…”
Section: Introductionmentioning
confidence: 99%